2020
DOI: 10.3390/cells9030558
|View full text |Cite
|
Sign up to set email alerts
|

Src Inhibition Attenuates Liver Fibrosis by Preventing Hepatic Stellate Cell Activation and Decreasing Connective Tissue Growth Factor

Abstract: The SRC kinase family comprises non-receptor tyrosine kinases that are ubiquitously expressed in all cell types. Although Src is reportedly activated in pulmonary and renal fibrosis, little is known regarding its role in liver fibrosis. This study investigated whether the inhibition of Src protects against liver fibrosis. The expression of Src was upregulated in thioacetamide (TAA)-induced fibrotic mouse liver and cirrhosis of patients, and phospho-Src was upregulated during activation of hepatic stellate cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Ma et al reported that ampelopsin, a natural flavonoid, attenuated CCl 4 -induced mouse liver fibrosis and HSC activation by inducing autophagy (Ma et al 2019). Seo et al found that Src inhibition increased autophagy flux and alleviated liver fibrosis and HSC activation (Seo et al 2020). The protective effect of autophagy was contradictory to our results.…”
Section: Discussioncontrasting
confidence: 96%
“…Ma et al reported that ampelopsin, a natural flavonoid, attenuated CCl 4 -induced mouse liver fibrosis and HSC activation by inducing autophagy (Ma et al 2019). Seo et al found that Src inhibition increased autophagy flux and alleviated liver fibrosis and HSC activation (Seo et al 2020). The protective effect of autophagy was contradictory to our results.…”
Section: Discussioncontrasting
confidence: 96%
“…The interaction of Src with integrin αV is required for integrin αV-mediated Src activation and subsequent fibroblast migration [ 58 ]. The interaction of SFKs and integrins plays critical roles in the development of lung fibrosis [ 59 , 60 , 61 ], liver fibrosis [ 62 , 63 ], and chronic kidney disease [ 64 ]. SFKs seem to play critical roles in the development of lung fibrosis, and the signaling involved may represent a novel opportunity to target fibrotic diseases [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the wild type (WT) mice, Src inhibitors (saracatinib and PP2) markedly suppressed the expression of α-SMA in HSCs and decreased the TGF-β-induced CTGF expression by increasing autophagy flux in hepatocytes. However, in primary hepatocytes of hepatocyte-specific Atg7 KO mice (Atg7 f/f Alb-Cre + ), Src inhibitors-induced autophagy and increased CTGF levels did not occur 45 . Thus, there is still a substantial gap between the current understanding of the potential roles of autophagy deficiency in the progression of liver fibrosis and whether Atg5 and Atg7 can be used as effective targets for the treatment of liver diseases.…”
Section: Liver Fibrosis and Autophagymentioning
confidence: 98%